Prediction of fertilization potential of frozen spermatozoa of cattle and buffalo - KUMAR, SUBODH; SHARMA, ARJAVA (The Indian Journal of Animal Sciences, 2014)
Frozen semen of 12 bulls each of Karan Fries cattle and Murrah buffalo of varying conception rates (CR), after appropriate thawing and washing, was subjected to 200 inM platelet activating factor (PAF) treatment for 15 min at 38Â°C and 5% CO2 leveL Thereafter treated spermatozoa were subjected to zona free hamster oocyte penetration test and fertilization parameters, viz. sperm attached per ovum (SA/O), ova attached (OA), fertilization per cent (FP), fertilization index (FI) and polyspermic ova (PO) were evaluated. R1 values were highest for SA/O and FI in both the species. Regressing them jointly against observed CR, the values of intercept constant (a), regression coefficients (b1 and b) for SA/O and Fl were evaluated as 25.0615, 1.1706 and -2.9245 for cattle and -61.9162, 0.0771 and 93.2561 for buffalo. CR was predicted by fitting these values in simple linear regression equation Y=a+b1X1+b2X2, which, was significantly (P <0.01) correlated with the observed CR as revealed by sample and rank correlation coefficients.